2014
DOI: 10.1111/area.12102
|View full text |Cite
|
Sign up to set email alerts
|

Noise inGuangzhou: the cultural politics of underground popular music in contemporaryGuangzhou

Abstract: Popular music in Guangzhou can be considered as a noise that applies social and political power to challenge the mainstream aesthetics and ideologies, rather than a low culture that lacks aesthetics. The main purpose of this article is to examine the cultural politics of underground popular music in contemporary Guangzhou, drawing on the analysis of its lyrical and sonic meanings through three genres: campus rock/pop, Canton‐rock and urban folk songs. Different types of underground popular music in Guangzhou e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Qian et al (2012) have examined the resistance shown by its residents to the promotion of Mandarin agendas on local television programmes and have explored how residents negotiated their urban identity. In the same location, Liu (2014) has considered underground music as an urban subculture, challenging the mainstream aesthetics and ideologies and creating regional noncommercial popular music.…”
Section: Key Insightsmentioning
confidence: 99%
“…Qian et al (2012) have examined the resistance shown by its residents to the promotion of Mandarin agendas on local television programmes and have explored how residents negotiated their urban identity. In the same location, Liu (2014) has considered underground music as an urban subculture, challenging the mainstream aesthetics and ideologies and creating regional noncommercial popular music.…”
Section: Key Insightsmentioning
confidence: 99%
“…This would not happen without the privatisation of ownership, with the co-existence of state-owned music affairs and the market-oriented pop music sector. According to C. Liu (2014), Cantopop and Manopop from Hong Kong and Taiwan were imported to fill the cultural vacuum (see discussion in Clark et al, 2016). During the late 1980s, Shaanxi folk songs (Northwest Wind) became the first prominent local popular music in China, followed by rock and roll.…”
Section: The Cultural Adaptation Modelmentioning
confidence: 99%
“…It adopted a cultural adaptation model from 1979 to 1991 when copyright was not in place, exploiting well-tested hits in markets outside mainland China, namely to produce cover songs. It provides a necessary annotation to the golden 30 years of the Chinese record industry since the first 10 years were not subject to copyright regulation (C. Liu, 2014). I use 'cultural adaptation' instead of 'shanzhai', due to the persistent postcolonial discourse of a low-income country tactically learning from its western counterparts within an imbalanced world order (see Chen, 2018a).…”
Section: The Cultural Adaptation Modelmentioning
confidence: 99%
“…At the micro-level of performative scenes, the sheer proximity between producers and patrons in live houses indicates an equal status of both sides, inviting communication and making both sides contributors to a rock milieu. In cities, live houses stimulate what Small (2011) calls musicking practices, through which producers and audience members sense each other and imagine alternatives (Liu, 2014), and the space itself becomes 'formative of the sounding and resounding of music' (Leyshon et al, 1995;Wood et al, 2007: 424). Curators of live houses reiterate the terms 'consciousness', 'Rock and Roll ethos' and 'utopia' (interview 2014).…”
Section: Live Rock Scene As a Small Commons In The City Web Of Empowe...mentioning
confidence: 99%